Critical Discourse Analysis of Hoaxes and Misinformation on Social Media in the Post-Truth Era - Ruthertati Sianturi; Monika Br. Tobing; Flora Gracia Siallagan; Nayla Azahra; Muhammad Natsir (Student Scientific Creativity Journal, 2026)
The phenomenon of hoaxes and misinformation on social media is growing stronger in the post-truth era, when the boundary between facts and opinions becomes blurred and public trust is more influenced by emotions and social relations compared to information verification. This condition not only impacts the quality of information but also shapes the way individuals understand their social reality. This study aims to examine in depth the construction of hoax and misinformation discourse and how individuals interpret, respond to, and reproduce such information in everyday life. The research uses a qualitative approach with a Critical Discourse Analysis (CDA) design. Data were collected through in-depth interviews, digital participatory observation, and document analysis of 12–15 participants who are active social media users. Data analysis was conducted using a thematic approach integrated with the CDA framework to reveal the dimensions of text, discursive practices, and social practices. The research findings show three main patterns, namely fragile trust in social relations, the dominance of emotions as the basis for interpreting information, and the normalization of hoaxes in everyday digital interactions. These findings reveal that hoaxes are not merely understood as incorrect information, but as part of a social experience that is negotiated through emotions and relationships. Theoretically, this study enriches discourse analysis studies by affirming the affective and relational dimensions in meaning construction. Practically, this study provides implications for strengthening digital literacy, developing public communication policies, and more contextual educational approaches in facing the challenges of misinformation in the digital era.